Comparative morphology of the gastrointestinal tract of white edible bird's nest swiftlet (Aerodramus fuciphagus [Thunberg]) and house swift (Apus nipalensis [Hodgson]) - Mat Amin, Fhaisol (2014)
A. fuciphagus or White Edible bird’s-nest Swiftlet (EBN Swiftlet) and A. nipalensis or House swift belong to Apodidae family. A. fuciphagus is the only bird in the world constructing its nest using saliva, whereas A. nipalensis builds its nest using grass and saliva as adhesive materials. The objective of this study is to evaluate the macro and microscopic morphology of the gastrointestinal tract of six selected male A. fuciphagus and four selected male A. nipalensis. The birds were caught in Kuala Terengganu, Terengganu, and in FELDA Redong, Segamat, Johore, using mist net according to the FAO standards, and were transported and immediately euthanized by injecting pentobarbital sodium (Nembutal®) at 80 mg/kg body weight through a brachial ulnar vein upon arrival at the Anatomy Laboratory, Faculty of Veterinary Medicine UPM. The body weight and length and the gastrointestinal tract (GIT) weight and length of each bird were measured, recorded and calculated into relative GIT weight and length. These values were analyzed using Mann-Whitney U Test for non-parametric data. The GIT specimens were then fixed in Bouin’s solution and underwent various processes for histomorphological and histomorphometrical evaluations. The histological evaluations include the used of H&E, Masson trichrome, Van Gieson, Gomori trichrome. Periodic acid-Schiff (PAS), Aldehyde fuchsin, Alcian blue pH 1.0 and pH 2.5, Aldehyde fuchsin-Alcian blue (AF-AB) and Periodic acid-Schicff-Alcian blue (PAS-AB) were used to determine and classify the type of mucins. Histomorphometric evaluations were also conducted on koilin thickness, villus height, and crypt depth, thickness of the tunica muscularis externa and goblet cell of the intestines. It was observed that the tongue had a sharp burficated apex, the esophagus was an elongated tubular structure with absence of crop and it continuously connected to the proventriculus, ventriculus and small intestine. The ventriculus was formed by a thick and strong muscle, whereas the intestines lacked both a cecum and Meckel’s diverticulum. All the recorded weight and length of the GIT and its glandular organs of A.fuciphagus were found to be smaller (P≤0.05) than those of A.nipalensis, except for the esophagus and pancreas. However, when calculated based on the relative weight and length, all the GIT and its glandular organs of A.fuciphagus were found to be significantly greater (P≤0.05) than those of A.nipalensis, except for the esophagus and pancreas. The tissue arrangement of the GIT in both Apodidae species consisted of mucosa at the innermost layer, with absent of the muscularis mucosa. It was followed by a submucosa rich in glandular structure, the tunica muscularis externa, comprised of inner longitudinal and outer circular muscle, and finally the serosa as the outermost layer. The tongue of both species of birds was comprised of a keratinized squamous epithelium, which was found to be thicker in the dorsal than ventral region. The submucosa layer consisted of a massive glandular structure, absent in the apical region of the tongue. The mucins were detected in the glands of the tongue and also along the GIT of A. fuciphagus and A. nipalensis. The lingual and esophageal glands of A. fuciphagus consist of acid carboxylated mucins, but A. nipalensis had a mixture of carboxylated and sulfated mucins. Along the GIT, the type of mucins was considerably similar. In turn, the thickness of koilin, height of the villus, crypt depth,thickness of the tunica muscularis externa and goblet cells in the intestinal segments were found to be significantly different (P≤0.05) in both A. fuciphagus and A. nipalensis. As a conclusion, the significant differences (P≤0.05) in the morphology of the GIT of A. fuciphagus and A. nipalensis are related to both the type of diet and the nest building ability.